PEMBERDAYAAN SOSIAL EKONOMI PEREMPUAN MARJINAL DI RUMAH SUSUN BANDARHARJO KOTA SEMARANG - Nada Nedia; Laila Kholid Alfirdaus (Journal of Politic and Government Studies, 2026)
Women’s empowerment is important to study because women remain in a vulnerable position due to structural inequalities that limit their access to economic resources, basic services, and decision-making spaces. This vulnerability is particularly evident among marginalized women living in densely populated urban areas, such as the women residents of the Bandarharjo Public Housing Complex in Semarang, who rely on the informal sector and face limited access to empowerment programs. This study aims to evaluate the policy framework underpinning empowerment, identify program implementation, and examine the program’s impact on the transformation of marginalized women’s groups.The study employs a qualitative method with a critical approach, with data collection through field observations, in-depth interviews, and documentary analysis. Findings indicate that although Semarang Municipal Act No. 7 of 2023 was enacted as the legal framework, its implementation has not targeted specific settings and relies heavily on administrative requirements. Various empowerment programs exist, but their reach is limited by administrative data mechanisms; women’s participation remains passive. Structural transformation remains unachieved, as programs merely enable adaptation to vulnerability without altering women’s power dynamics or social positions.